(3QSGdI GHf GdYQHi Edi aNQ GdedI hGdOjf eMeO Hf YeQ GdNWjHs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO dgd hSdGeg Ydi YHGOg CeG HYO aGfG fMeO Gdjc Gdgd GdPi dG Edg EdG gh s
(3BNQgG (B:s
(3hcfJ CQjO Cf CPcQ GdNdhI hTQhWgG hGdgd hdi GdcaGjI s
(3Vef eLehY , JQJjHgG (B: (3GdSGHY hGdYTQhfs
(3GfXQ GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds